(untitled) (African Journal of Biomedical Research, 2023)
Healthy living is fundamental to a socially and economically productive life and good utilization of healthcare services is pivotal to improving the health status of the population. This study assessed the pattern of health care service utilization (which is a precursor to health status) among residents of a community in Ibadan. This study employed the mixed-methods cross-sectional study design. Multi-stage sampling technique was used to recruit 296 adult residents of the community after due process of community entry. A semi-structured interviewer-administered questionnaire and Key-informant interview guide were developed and used to elicit information from the respondents. Descriptive statistics, Fishers’ exact and Chi-square tests were used to analyze the quantitative data and the level of statistical significance was set at α ≤ 0.05. Thematic analysis was used to analyze the qualitative data. Respondents’ mean age was 36.9±13.5 years. Common health issues experienced in the community included malaria (28.4%), headache (15.3%), fever (12.5%) and body pain (12.5%). Majority (85.1%) of the respondents sought for care when they felt unwell, using various means like private hospitals and patent medicine stores. Many factors were identified by respondents to be responsible for their health seeking behaviours. Utilisation of orthodox healthcare facilities was low among residents due to cost, unavailability of and distance to available government facilities. Therefore, there is a need for collaborative efforts by the government, healthcare policy makers, healthcare workers and community leaders to provide healthcare facilities and educate the community members on the need for positive health-seeking behaviour